2002
DOI: 10.1139/o01-212
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of lactoferrin

Abstract: This paper reviews our current knowledge of the structure and function of the iron-binding protein lactoferrin. In particular, it attempts to relate the various proposed physiological functions of lactoferrin to its most characteristic biochemical properties, i.e. its ability to bind iron and its highly basic nature. The extent to which various physiological functions can be considered as definitely established is critically reviewed, and suggestions for future research are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
250
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(254 citation statements)
references
References 54 publications
1
250
0
3
Order By: Relevance
“…Lactoferrin is known to have bactericidal, fungicidal, and antiviral activity as well as antitumor, anti-inflammatory and immunoregulatory properties as described in several review articles [27,28,29,30]. Most of these activities reside in the N-domain of lactoferrin [31].…”
Section: Resultsmentioning
confidence: 99%
“…Lactoferrin is known to have bactericidal, fungicidal, and antiviral activity as well as antitumor, anti-inflammatory and immunoregulatory properties as described in several review articles [27,28,29,30]. Most of these activities reside in the N-domain of lactoferrin [31].…”
Section: Resultsmentioning
confidence: 99%
“…Lactoferrin (LF) is an 80 kg·mol −1 member of the transferrin family of iron-binding glycoproteins, which was originally found in mammalian exocrine secretions and in specific granules of polymorphonuclear leukocytes [3,11]. Human LF (hLF) is present at high concentrations (average 1 to 3.2 mg·mL −1 ) and plays a significant protective role in human milk.…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin possesses a wide range of immunomodulatory activities [17][18][19] [20] [21] including promotion of the T-cell dominated DTH response towards BCG antigens [22,23], The ability of lactoferrin to enhance the generation of antigen specific DTH responses suggests that lactoferrin could promote development of specific T-cell responses against a complex antigen, such as BCG [24,25] The development of T-cell helper type 1 (T H 1) immunity is, in part, regulated by production of IL-12 [26,27]. A variety of in vivo studies have shown lactoferrin capable of increasing production of IL-12 [28][29][30].…”
Section: Introductionmentioning
confidence: 99%